Air and medium temperatures for Alstroemeria 'Atlas' and 'Monika' - Keil, Linda Sue, author; Goldsberry, Kenneth L., advisor; Hanan, Joe J., committee member; Ross, Cleon, committee member (Colorado State University. Libraries, 1987)
Alstroemeria cultivars 'Atlas' and 'Monika' were grown in four 25.4 m2 fiberglass-covered greenhouse compartments at the W.D. Holley Plant Environmental Research Center, Colorado State University. Each compartment contained two raised redwood benches subdivided into four 75 x 105 cm plots with buffer zones at either end of the bench, Individual benches had replicated plots of cooled and noncooled substrate treatments. The cooled plots contained seven loops of .625 cm OD Biotherm tubing buried 15 cm beneath the pea gravel surface. A thermostatically-controlled cooling system supplied cold water, upon demand, in an attempt to maintain a medium temperature of 11°C. Compartments were heated to 10° to 11°C during night periods, and the following daytime temperature regimes were established: Compartment A, 14° to 20°C; Compartment B, 20° to 26°C; Compartment C, 23° to 28°C; and Compartment D, 17° to 23°C. A night break was provided with incandescent lamps when natural daylengths were less than 12 hours. Developing cultivar rhizomes were transferred from 10 cm pots to the bench plots on November 18, 1985. The first flower data were taken on February 10, 1986, then collected every other day and summarized weekly during the next 52 weeks. Parameters measured included: stem length, flower grade, and total production. Data were analyzed as a split-split plot design with media treatments randomized within each pair of plots. Total flower production of 'Atlas' in all compartments was 1.6 times as great as 'Monika'. Significantly larger numbers of flower stems were produced in the cooled substrate of compartments A and D. The results provided evidence that the greatest production of 'Atlas' and 'Monika' occurred with average daytime temperatures of 20°C combined with an average medium temperature of 12°C to 14°C. Consequently, the cooled medium treatment coupled with cooler air temperatures allowed production to continue virtually year-round. The warmer daytime temperatures of compartments B and C increased the flower quality. However, the higher production in compartments A and D far outweighed the advantage that warmer temperatures contributed to quality. The flower quality of 'Monika' was considerably less than that of 'Atlas' in all temperature treatments. Warmer daytime temperatures also contributed to longer stems. 'Atlas' and 'Monika' stems from compartment C averaged a maximum of 13 cm longer than those from the remaining compartments. 'Atlas' stems were significantly longer than those of 'Monika' in all compartments. A five week sub-trial was conducted to determine air temperature effects on Alstroemeria inflorescence characteristics. Parameters measured included: number of cymes per stem, cyme length, stem thickness, and number of buds per cyme. Data were analyzed as a split plot design. No significant differences were observed for number of cymes per stem and stem thickness between compartments, although 'Atlas' had thicker stems than 'Monika'. A significant trend toward increasing cyme length with increasing daytime temperature was evident in both cultivars. Significantly more buds were produced on stems of both cultivars in compartment D (i.e., 20°C average day air temperature) compared to all other compartments.
Covers not scanned.
Keywords: Lilies -- Analysis